The Role of the University in the Implementation of Eco-Innovation at the Creative Industry Center of Natural Stone Crafts - Astuti, Murti; Prawoto, Pratikto; Irawan, Yudy Surya; Sugiono, Sugiono; Saleh, S. M. (International Journal of Integrated Engineering, 2019)
This study aims to find out the influence of the university's role on the implementation of eco-innovation in the creative industry in the natural stone handicraft sector. The object of this research is the creative industry center of the marble and natural stone handicraft sub-sector in TulungagungCity, Indonesia. From the existing craftsmen population, 81 craftsmen as respondents were taken as samples. The research data was obtained by distributing questionnaires, then the data were tested, processed and analyzed using Partial Least Square Consistent - Structural Equation Modeling (PLS-SEM).The results of this study states that the role of the university in the implementation of eco-innovation in the industry center of natural stone handicraft in Tulungagung can significantly improve eco-organizational innovation, eco-process innovation and eco-marketing innovation, but not significant in improving eco-product innovation. To further improve the implementation of eco-product innovation, what needs to be improved is the role of the university in assisting to increase eco-marketing, because of its significant influence on eco-product innovation. The results of this study will later be developed to explain the concept of triple helix, namely the role of University, Industry and Government in the implementation of eco-innovation and the improvement of the performance of creative industrial centers of natural stone crafts in Tulungagung Indonesia.